Impact of the training program on lipid profile and cardiac health - Burneiko, R. C.; Diniz, Y. S.; Faine, L. A.; Galhardi, C. M.; Padovani, C. R.; Novelli, ELB; Cicogna, A. C. (Sociedad Biolgia Chile, 2004)
The aim of this study was to investigate the effects of training programs on serum lipid profile and myocardial oxidative stress. Male Wistar rats (2 mo-old) were divided into three groups (n=8): sedentary (S), loadless trained (T) and trained-overload 2% body weight (TL). T and TL were trained through swimming for 9 weeks. T and TL rats had increased myocardial lipoperoxide (TBA) and lipid hydroperoxide (HP), whereas HP was higher in TL than in T animals. Superoxide dismutase (SOD) activities were lowest in TL. Myocardial glutathione peroxidase (GSH-Px) was lower in TL than in T and S rats. TL decreased HDL-cholesterol and increased LDL-cholesterol. The serum lactate dehydrogenase and TBA were increased, while SOD and GSH-Px activities were decreased in TL rats. Loadless training was able to improve HDL-cholesterol and to reduce LDL-cholesterol. In conclusion, the loadless training program induced beneficial effects on lipid profile, while overload training induced dyslipidemic profile that was associated with serum oxidative stress. The overload training program was deleterious relative to loadless training program, increasing myocardial oxidative stress.
Keywords: training; lipid profile; oxidative stress; heart; serum